Pengaruh Jarak Tanam Dan Dosis Pupuk Terhadap Pertumbuhan dan Produksi Padi Sawah (Oryza sativa l.) Dengan Metode Sri - Marzuki '; Murniati '; Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The plant of paddy field (Oryza sativa L.) is food plant which very important in Indonesia, because as staple food and availability must fulfilled in year-round. Several factors cause of low production and paddy field productivity including occurs over the land, paddy seed used to local varieties and the use of fertilizer not the recommended. This research aims to know about the best of spacing and fertilizer dose to growth and paddy field production (Oryza sativa L.) with SRI method. This research implemented in rice foundation of horticultural hall land, Kaharuddin Nasution street, Marpoyan desert, Pekanbaru. This research implemented during 4 months who started in january 2013 until april 2013 . The result show that spacing and fertilizer dose in each treatment able to increase a growth and paddy field production with SRI method. By observing the response of paddy after provision of treatment through parameter, it can be concluded that the best treatment is use of spacing 25 cm x 25 cm and Urea Fertilizer 400 kg/ha + Sp-36 200 kg/ha + KCl 200 kg/ha, because able to give a good response to harvest parameter and highest milled rice per plot. keywords : paddy , SRI , fertilizer dose .